Biologics in the Treatment of Lupus Erythematosus: A Critical Literature Review. (18th July 2019) - Samotij, Dominik; Reich, Adam
Abstract : Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease affecting multiple organ systems that runs an unpredictable course and may present with a wide variety of clinical manifestations. Advances in treatment over the last decades, such as use of corticosteroids and conventional immunosuppressive drugs, have improved life expectancy of SLE sufferers. Unfortunately, in many cases effective management of SLE is still related to severe drug-induced toxicity and contributes to organ function deterioration and infective complications, particularly among patients with refractory disease and/or lupus nephritis. Consequently, there is an unmet need for drugs with a better efficacy and safety profile. A range of different biologic agents have been proposed and subjected to clinical trials, particularly dedicated to this subset of patients whose disease is inadequately controlled by conventional treatment regimes. Unfortunately, most of these trials have given unsatisfactory results, with belimumab being the only targeted therapy approved for the treatment of SLE so far. Despite these pitfalls, several novel biologic agents targeting B cells, T cells, or cytokines are constantly being evaluated in clinical trials. It seems that they may enhance the therapeutic efficacy when combined with standard therapies. These efforts raise the hope that novel drugs for patients with refractory SLE may be available in the near future. This article reviews the current biological therapies being tested in the treatment of SLE.